Triphasic versus monophasic oral contraceptives for contraception - Van Vliet, Huib AAM (Cochrane Database Syst Rev, 2011)
BACKGROUND: Side effects of oral contraceptive (OC) pills discourage adherence to and continuation of OC regimens. Strategies to decrease adverse effects led to the introduction of the triphasic OC in the 1980s. Whether triphasic OCs have higher accidental pregnancy rates than monophasic pills is unknown. Nor is it known if triphasic pills give better cycle control and fewer side effects than the monophasic pills. OBJECTIVES: To compare triphasic OCs with monophasic OCs in terms of efficacy, cycle control, and discontinuation due to side effects. SEARCH METHODS: We searched the computerized databases of the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library), MEDLINE, POPLINE, EMBASE, and LILACS, as well as clinical trials databases (ClinicalTrials.gov and the World Health Organization Clinical Trials Registry Platform (ICTRP)) in May 2011. Additionally, we searched the reference lists of relevant articles. We also contacted researchers and pharmaceutical companies to identify other trials not found in our search. SELECTION CRITERIA: We included randomized controlled trials (RCTs) comparing any triphasic OC with any monophasic pill used to prevent pregnancy. Interventions had to include at least three treatment cycles. DATA COLLECTION AND ANALYSIS: We assessed the studies found in the literature searches for possible inclusion and for their methodological quality. We contacted the authors of all included studies and of possibly randomized trials for supplemental information about the methods used and outcomes studied. We entered the data into RevMan and calculated odds ratios for the outcome measures of efficacy, breakthrough bleeding, spotting, withdrawal bleeding and discontinuation. MAIN RESULTS: Of 23 trials included, 19 examined contraceptive effectiveness. The triphasic and monophasic preparations did not differ significantly. About half of the included trials reported favorable bleeding patterns, that is less spotting, breakthrough bleeding or amenorrhea, in triphasic versus monophasic OC users. However, meta‐analysis was generally not possible due to differences in measuring and reporting the cycle disturbance data as well as differences in progestogen type and hormone dosages. No significant differences were found in the numbers of women who discontinued due to medical reasons, cycle disturbances, intermenstrual bleeding or adverse events. AUTHORS' CONCLUSIONS: The available evidence is insufficient to determine whether triphasic OCs differ from monophasic OCs in effectiveness, bleeding patterns or discontinuation rates. Therefore, we recommend monophasic pills as a first choice for women starting OC use. Large, high‐quality RCTs that compare triphasic and monophasic OCs with identical progestogens are needed to determine whether triphasic pills differ from monophasic OCs. Future studies should follow the recommendations of Belsey or Mishell on recording menstrual bleeding patterns and the CONSORT reporting guidelines.